Sociodemographic Characteristics of Tuberculosis Cases From Rural Areas in Yogyakarta - Purwanti, Sri; Nugroho, Andri Setyo Dwi; Maula, Ahmad Watsiq (BKM Public Health and Community Medicine, 2024)
Purpose: Tuberculosis (TB) remains a public health challenge. In 2023, the number of TB cases in Yogyakarta reached 6079 cases, of which 1,166 (19.2%) were in rural areas. Being in rural areas is often a risk factor for TB incidence due to several aspects. An initial step to determine the sociodemographic characteristics of TB patients in Yogyakarta is important to analyze the situation in control efforts. Methods: This study is a descriptive cross-sectional study using secondary data based on SITB (Tuberculosis Information System) of the Yogyakarta Provincial Health Office. Data were collected from January to December 2023. The classification of rural areas is based on the classification of data from the Central Statistic Agency (BPS). Results: Based on the analysis conducted, it is known that the majority of 665 (57%) TB patients in rural areas are male, 26 (2.23%), 300 people (29%) are not working, 535 (45.8%) from Gunung Kidul, 703 (60.29%) seek treatment at the hospital, 450 (38.6%) at the health center, and others at clinics / independent practitioners. A total of 1038 (89.02%) were diagnosed with Pulmonary TB and 128 (10.98%) were diagnosed with Extra Pulmonary TB, 752 (64.49%) were clinically confirmed and 414 (35.51%) were bacteriologically confirmed, 717 (61.49%) TB patients in rural areas did not know their Diabetes, 973 (83.45) did not know their HIV status and 26 (2.23%) had not received standards TB treatment. Conclusion: The problem of Tuberculosis in rural areas still needs attention considering the high economic burden due to the inability of TB patients to work, as well as the low proportion of Diabetes and HIV testing as a leading collaborative program in TB control.